THE INFLUENCE OF CULTURE, BELIEFS AND EXPERIENCE ON THE SUSTAINABLE END-OF-LIFE MANAGEMENT OF BUILDINGS IN NIGERIA - Aminu Lawan ABDULLAHI; Angela LEE (Journal of Construction Project Management and Innovation)
While it is usually believed that economic incentives are behind waste management practices in developing countries, this article discusses culture, belief and experience as the other major influences in the management practices of building demolition waste in Nigeria. Practitioners in the building demolition sub-sector were interviewed to identify the influences that contribute to the emergence of reuse as a preferable demolition waste management technique in society, in addition to the economic incentives. This study will give an insight into some practices in a pre-industrial society with potential for recognition and contribution of the development of formal waste management systems in developing countries.